Extended depth‐of‐focus toric intraocular lens targeted for binocular emmetropia or slight myopia in the nondominant eye: Visual and refractive clinical outcomes. Issue 10 (October 2019) - Sandoval, Helga P.; Lane, Stephen; Slade, Stephen; Potvin, Richard; Donnenfeld, Eric D.; Solomon, Kerry D.
Abstract : Purpose : To compare the visual and refractive outcomes with a diffractive toric extended depth‐of‐focus (EDOF) intraocular lens (IOL) when both eyes are targeted for emmetropia and the nondominant eye is targeted for slight myopia. Setting : Three clinical practices, United States. Design : Prospective case series. Methods : Patients having routine cataract surgery with bilateral Tecnis Symfony toric EDOF IOL implantation were assigned to 1 of 2 groups. In 1 group, the nondominant eye was targeted for −0.50 diopter (D) (mini‐monovision). Assessments included uncorrected monocular and binocular visual acuities (logarithm of the minimum angle of resolution) at distance (4 m), intermediate (66 cm), and near (40 cm) and the postoperative residual refractive error. Results : Forty patients were enrolled in each group, with 1 dropout. The mean postoperative residual refractive astigmatism was 0.25 D in both groups, with no statistically significant difference. The mean residual refractive astigmatism was 0.50 D or lower in 92% of eyes (72/78) in the mini‐monovision group and 95% of eyes (74/78) in the emmetropia group 3 months postoperatively. The mini‐monovision group had slightly worse uncorrected visual acuity at 4 m than the emmetropia group (0.16 versus 0.09; P = .002) but better uncorrected acuity at 40 cm (0.25 versus 0.34; P < .001). Binocular uncorrected acuity was not statistically significantly different between groups at 4 m (−0.03 versus −0.01; P = .33) or 66 cm (0.06 versus 0.04; P = .34) but was statistically significant at 40 cm (0.25 versus 0.19; P = .03). Conclusions : The EDOF toric IOL provided functional distance, intermediate, and near vision. A slight monovision approach appears to improve near visual acuity.